2022
DOI: 10.1111/os.13279
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet‐Rich Plasma in Anterior Cruciate Ligament Reconstruction: A Systematic Review of Randomized Controlled Trials

Abstract: This study aimed to identify the effectiveness of platelet-rich plasma (PRP) for patients operated with anterior cruciate ligament reconstruction (ACLR). Databases of PubMed, Embase, and CENTRAL were independently retrieved by two authors, for identifying the eligible randomized controlled trials (RCTs) comparing the clinical and imaging outcomes of ACL reconstructed patients augmented with or without PRP. The Cochrane Collaboration tool was utilized to assess the risk of bias of the included trials. We qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(308 reference statements)
0
5
0
Order By: Relevance
“…Recently, several systematic reviews of RCTs reached a consensus that intraoperative injection of PRP is ineffective in improving long-term PROs, knee stability, or radiologic outcomes at more than 6 months after ACLR despite different results for short-term outcomes . Similarly, the 12-month clinical and radiologic outcomes of the present study showed no long-term efficacy of postoperative PRP injection in patients who underwent ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several systematic reviews of RCTs reached a consensus that intraoperative injection of PRP is ineffective in improving long-term PROs, knee stability, or radiologic outcomes at more than 6 months after ACLR despite different results for short-term outcomes . Similarly, the 12-month clinical and radiologic outcomes of the present study showed no long-term efficacy of postoperative PRP injection in patients who underwent ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis with pooled follow-up periods showed improved Lysholm and visual analog scale scores in the PRP group; the between-group differences were statistically but not clinically significant. Furthermore, the discrepant biological hypotheses and sites of PRP administration resulted in diverse and incomparable radiologic outcomes among studies, including graft remodeling, tunnel enlargement, and harvest site healing . In terms of graft remodeling, only 1 RCT with intra-articular injection and 1 RCT with intratunnel and intragraft injection reported improved short-term MRI results at 4 to 6 months and 4 to 6 weeks after ACLR, respectively, while the statistical significance diminished over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations